2022
DOI: 10.1002/ppul.26077
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of intermittent dosed intravenous vancomycin in adult persons with cystic fibrosis

Abstract: Background Antibiotics have altered pharmacokinetics (PK) in persons with cystic fibrosis (PwCF) during treatment for an acute pulmonary exacerbation (APE). The Cystic Fibrosis Foundation Pulmonary Guidelines–Treatment of Pulmonary Exacerbations do not provide specific recommendations for treatment of methicillin‐resistant Staphylococcus aureus (MRSA) lung infections. However, the American Thoracic Society Guidelines recommend vancomycin as the first‐line therapy. Only one study has previously described a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…We utilized TDM to calculate CL vanco and AUC:MIC for each patient. The CL vanco was similar to a previous study by Lindley et al, 15 which reported a mean CL vanco of 5.11 L/h for intermittent dosed IV vancomycin in adult PwCF.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We utilized TDM to calculate CL vanco and AUC:MIC for each patient. The CL vanco was similar to a previous study by Lindley et al, 15 which reported a mean CL vanco of 5.11 L/h for intermittent dosed IV vancomycin in adult PwCF.…”
Section: Discussionsupporting
confidence: 90%
“…Pleasants et al 14 examined the PK of a single dose of IV vancomycin in a small group of adult PwCF and found similar volume of distribution (V d ) and vancomycin clearance (CL vanco ) to adults without CF. Lindley et al 15 described the PK of intermittent IV vancomycin at steady state in 13 adult PwCF and found similar results to that of Pleasants et al 14 We aimed to describe the PK of continuous infusion vancomycin in the adult PwCF being treated for a PEx at the University of Utah Adult Cystic Fibrosis Center. AKI was defined by the Risk, Injury, Failure, Loss, ESRD criteria and liver injury was defined as elevations of alanine transaminase, aspartate aminotransferase, or alkaline phosphatase that exceeded three times the upper limit of normal.…”
mentioning
confidence: 65%
See 3 more Smart Citations